2015
DOI: 10.1007/s10055-015-0266-4
|View full text |Cite
|
Sign up to set email alerts
|

Simulator sickness incidence and susceptibility during neck motion-controlled virtual reality tasks

Abstract: To determine the incidence, severity, and predisposing factors to simulator sickness (SS) when using the neck virtual reality (VR) device in asymptomatic individuals to understand the risk of provoking SS in the development of neck VR as a rehabilitation tool. Thirty-two participants used the VR system. Postural stability was measured before and after each VR module [range of motion (ROM), velocity, and accuracy]. The duration of each module was recorded, and participants reported their SS using a visual analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 51 publications
0
23
0
2
Order By: Relevance
“…According to other research efforts using Oculus Rift (POLCAR & HOREJSI 2013;Treleaven et al 2015), symptoms related to cybersickness episodes, such as nausea and headaches, were witnessed. This is a concern worth some consideration when developing further studies with the prototype.…”
Section: Discussionmentioning
confidence: 99%
“…According to other research efforts using Oculus Rift (POLCAR & HOREJSI 2013;Treleaven et al 2015), symptoms related to cybersickness episodes, such as nausea and headaches, were witnessed. This is a concern worth some consideration when developing further studies with the prototype.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to vividness and interactivity, one component that negatively contributes to presence is simulator sickness (Maraj et al 2017). Various experimental studies (e.g., Treleaven et al 2015;Draper et al 2001) have reported that the use of VR devices applying HMD can cause simulator sickness, which has a negative effect on presence. The analysis revealed that there are study results indicating relief from simulator sickness when the inputs entering the visual and vestibular organs are consistent based on the movement in a virtual space through actual walking and movement (Chance et al 1998).…”
Section: Literature Reviewmentioning
confidence: 99%
“…An attractive aspect of virtual reality (VR) is that it can be used to present visual stimuli under more realistic viewing conditions. However, VR introduces discomfort for an estimated 25-40% of individuals including motion sickness (e.g., [28]). In the current study, we have provided evidence that such discomfort arises from sensory cue conflicts, in particular, conflicts related to motion parallax cues.…”
Section: Discussionmentioning
confidence: 99%